Psychosocial roots of paranoid ideation: The role of childhood experiences, social comparison, submission, and shame. (9th May 2018) - Carvalho, Célia Barreto; da Motta, Carolina; Pinto‐Gouveia, José; Peixoto, Ermelindo
Abstract : Background: Social experiences have a significant impact on cognitive functioning and appraisals of social interactions. Specifically, recalls of antipathy from parents, submissiveness, and bullying during childhood can have a significant influence on paranoid ideation later in life. Method: Multiple hierarchical regression analysis was performed on a sample of 91 patients diagnosed with paranoid schizophrenia in remission and active phase, their first‐degree relatives ( n = 32) and unaffected controls ( n = 64). Objectives: Exploring the impact of distal (events from childhood) and proximal factors (current cognitive, emotional, and behavioural aspects of social functioning) in the frequency, degree of conviction, and distress resulting from paranoid ideation in the participants from 4 samples. Results: Proximal and distal factors (shame, submissive behaviour, negative social comparison, antipathy from father) predicted several aspects of paranoid ideation. Those variables had a differential impact in affected patients and healthy controls. Discussion: Finding suggests different variables being involved in paranoid ideation, and the specificities of patients with paranoid schizophrenia should be considered in the development of more effective psychotherapeutic interventions.